Estimation of the fake background for the doubly charged Higgs boson production in the ATLAS experiment - Floros,Georgios (2025)
The existence of doubly charged Higgs bosons (H±±) is predicted by several theories beyond the Standard Model that aim to explain the origin of neutrino masses. These particles are expected to decay into same-sign lepton pairs H±± → ℓ±ℓ±. At the LHC, they are produced predominantly via the Drell–Yan process, resulting in four-lepton final states. Due to the rarity of events involving doubly charged Higgs bosons, an accurate estimation of background contributions is crucial. This thesis focuses on estimating the fake-lepton background using the fake factor method. The analysis is based on 13 TeV ATLAS Open Data events with exactly one lepton, corresponding to an integrated luminosity of 10.06 ± 0.37 fb−1. Separate sets of fake factors were measured for electrons and muons in bins of transverse momentum and pseudorapidity to account for their kinematic dependence. The method was validated by closure tests performed separately for each lepton flavor in regions orthogonal to those used for measurement, but with the same lepton multiplicity. The predicted fake background shows agreement with the observed data at low pT, while discrepancies appear at high pT, likely due to unquantified systematic uncertainties.
Keywords: doubly charged Higgs boson; ATLAS; LHC; fake factor method